Dermatitis Artefacta - Pandu Haryo Jatmiko (Open Access Indonesian Journal of Medical Reviews, 2021)
Dermatitis artefacta, also known as factitial dermatitis, is a disease in which self- inflicted skin injury is utilized to fulfill a conscious or unconscious urge to play the sick part. It is more frequent in women and individuals who have an underlying mental illness or are under external stress. The diagnosis is one of exclusion, and it is sometimes difficult to establish since patien ts seldom acknowledge to playing a part in the development of their lesions. Treatment can be difficult, and treatment should rely on a multidisciplinary team comprised of dermatology and psychiatrist.